Expansion of mesenchymal stem cells under atmospheric carbon dioxide. (2nd September 2013) - Brodsky, Arthur Nathan; Zhang, Jing; Visconti, Richard P.; Harcum, Sarah W.
Abstract : Stem cells are needed for an increasing number of scientific applications, including both fundamental research and clinical disease treatment. To meet this rising demand, improved expansion methods to generate high quantities of high quality stem cells must be developed. Unfortunately, the bicarbonate buffering system – which relies upon an elevated CO2 environment – typically used to maintain pH in stem cell cultures introduces several unnecessary limitations in bioreactor systems. In addition to artificially high dissolved CO2 levels negatively affecting cell growth, but more importantly, the need to sparge CO2 into the system complicates the ability to control culture parameters. This control is especially important for stem cells, whose behavior and phenotype is highly sensitive to changes in culture conditions such as dissolved oxygen and pH. As a first step, this study developed a buffer to support expansion of mesenchymal stem cells (MSC) under an atmospheric CO2 environment in static cultures. MSC expanded under atmospheric CO2 with this buffer achieved equivalent growth rates without adaptation compared to those grown in standard conditions and also maintained a stem cell phenotype, self‐renewal properties, and the ability to differentiate into multiple lineages after expansion. © 2013 American Institute of Chemical Engineers Biotechnol. Prog ., 29:1298–1306, 2013